Habib Hadi's Leadership Transition in Probolinggo 2024 Election - Husni Mubaroq; Hasan Abdul Wafi (Universitas Islam Darul Ulum Lamongan, 2025)
Elections in Indonesia reflect the practice of popular sovereignty as stipulated in the 1945 Constitution and Law No. 7 of 2017. This study examines the leadership transition of Habib Hadi in the 2024 Probolinggo Mayoral Election. This transition mirrors the dynamics of local democracy, presenting challenges in ensuring the continuity of development programmes and upholding good governance. Based on charismatic and transformational leadership theories, the study explores the influence of Habib Hadi's leadership on public political participation, government stability, and sustainable development. The study employs a case study method with a qualitative approach through in-depth interviews and document analysis. The results indicate that while Habib Hadi has made positive contributions in various sectors, challenges in transparency and efficiency need to be addressed to strengthen leadership legitimacy.